2005
DOI: 10.1016/j.cell.2005.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The Cryo-EM Structure of a Translation Initiation Complex from Escherichia coli

Abstract: The 70S ribosome and its complement of factors required for initiation of translation in E. coli were purified separately and reassembled in vitro with GDPNP, producing a stable initiation complex (IC) stalled after 70S assembly. We have obtained a cryo-EM reconstruction of the IC showing IF2*GDPNP at the intersubunit cleft of the 70S ribosome. IF2*GDPNP contacts the 30S and 50S subunits as well as fMet-tRNA(fMet). IF2 here adopts a conformation radically different from that seen in the recent crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
291
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(318 citation statements)
references
References 64 publications
(71 reference statements)
22
291
2
3
Order By: Relevance
“…The foot-printing studies were done with 30S subunits and not tried with 70S ribosomes. As mentioned in the Introduction, evidence for IF3 presence on 70S ribosomes was reported (9). The overlapping binding sites on 30S and 70S (9) could be reconciled with a distinct binding region, whereas the binding site derived from a crystallographic study could not, because the C-terminal domain of IF3 was assigned to the upper end of the shoulder on the solvent side of 30S subunits of Thermus thermophilus (51).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The foot-printing studies were done with 30S subunits and not tried with 70S ribosomes. As mentioned in the Introduction, evidence for IF3 presence on 70S ribosomes was reported (9). The overlapping binding sites on 30S and 70S (9) could be reconciled with a distinct binding region, whereas the binding site derived from a crystallographic study could not, because the C-terminal domain of IF3 was assigned to the upper end of the shoulder on the solvent side of 30S subunits of Thermus thermophilus (51).…”
Section: Discussionmentioning
confidence: 84%
“…However, the in vivo concentration of IF3 is 100-fold less (8) than required for full dissociation of 70S in vitro (4). Evidence for the presence of IF3 on 70S ribosomes was reported (9), indicating that the functional spectrum of IF3 is possibly not restricted to an antiassociation effect. Both IF3 and IF2 are also responsible for the fidelity of decoding the initiation AUG by fMet-tRNA Met f at the P site of 30S subunits (10).…”
mentioning
confidence: 99%
“…11,14 Thus, a majority of structural data connect uL11 with the elongation cycle of protein synthesis. However, several structural analyses implicate this protein in interaction with IF2 and RF3, indicating involvement of uL11 in the initiation and termination steps of translation, 15,16 which is also supported by several functional analyses. 17,18 The large ribosomal subunit depleted of this protein is able to bind initiation factor IF2 in vitro but it cannot stimulate GTP hydrolysis required for the subunit joining.…”
Section: Introductionmentioning
confidence: 85%
“…This process is undertaken by eIF5B, a partial homologue of eubacterial IF2, but more closely related to archaeal aIF5B. The structural details of how eIF5B could concurrently check for both the presence of tRNAi and the sarcin-ricin loop in the context of the large ribosomal subunit had only previously been established at low resolution for the partial bacterial homologue, IF2, which functions in a somewhat different manner [22,23]. Two key cryo-EM structures [24,25], in conjunction with an important crystallographic study of the ribosome [26], have revealed the mechanism by which this takes place.…”
Section: Incorporating the Large Subunit: Coming Full Circlementioning
confidence: 99%